2008
DOI: 10.1007/s10591-008-9078-y
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Supervisor and Supervisee Matching, Role Conflict, and Supervisory Relationship on Supervisee Satisfaction

Abstract: In this study we explore how the ''match'' between supervisor and supervisee on contextual variables affects both conflict and the working alliance, which affects supervisee satisfaction. Participants included 132 supervisees in academic programs nationwide. The extent of match between supervisor and supervisee characteristics was not found to impact conflict, the working alliance, or supervisees' satisfaction with supervision. Working alliance was highly predictive of supervisee satisfaction. Despite the find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 28 publications
(27 reference statements)
0
36
0
4
Order By: Relevance
“…As measured by the S‐SRQ, the SR was associated with satisfaction with supervision and IoS and effectiveness and accounted for a substantial and significant amount of variance in these variables. This supports previous research showing that good SRs are important in determining satisfaction with supervision and higher perceived effectiveness of supervision (Britt & Gleaves, ; Cheon et al ., ; Ladany et al ., ; Palomo et al ., ; Watkins, , ). Supervisee's satisfaction with supervision thus remains an important outcome to measure in supervision research (Ellis & Ladany, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As measured by the S‐SRQ, the SR was associated with satisfaction with supervision and IoS and effectiveness and accounted for a substantial and significant amount of variance in these variables. This supports previous research showing that good SRs are important in determining satisfaction with supervision and higher perceived effectiveness of supervision (Britt & Gleaves, ; Cheon et al ., ; Ladany et al ., ; Palomo et al ., ; Watkins, , ). Supervisee's satisfaction with supervision thus remains an important outcome to measure in supervision research (Ellis & Ladany, ).…”
Section: Discussionmentioning
confidence: 99%
“…Supervisee satisfaction with supervision has been widely used as an outcome measure in supervision research (Ellis & Ladany, ). The SR is a good predictor of supervisee satisfaction (Cheon, Blumer, Shih, Murphy, & Sato, ; Ramos‐Sanchez et al ., ). Britt and Gleaves () found that ‘collaboration and mutual understanding’, key components of a good SR, was the best predictor of satisfaction with supervision.…”
Section: Introductionmentioning
confidence: 99%
“…There is a well‐replicated finding that the quality of the supervisory alliance is associated with supervisee satisfaction with supervision (Bernard & Goodyear, 2009; Ladany, Ellis, & Friedlander, 1999). Specifically, the extent to which the supervisor is perceived by the supervisee as empathic and supportive is associated with supervisee satisfaction, and this effect is independent of the match between contextual variables (e.g., age, gender, and theoretical orientation) of the supervisor and supervisee (Cheon, Blumer, Shih, Murphy, & Sato, 2009; Gray et al., 2001; Riess & Herman, 2008). However, the association of satisfaction and supervisory alliance is a correlation, and it is unclear if this association is causal.…”
Section: The Effectiveness Of Supervisionmentioning
confidence: 97%
“…This is also supported by findings from [15] there is a relationship between supervisory working alliance and supervision satisfaction. According [16], the supervisory working alliance is correlated to the supervisees' satisfaction. In addition, there is a research which indicated the significant relationship between supervisory working alliance and counselor performance [17].…”
Section: Discussionmentioning
confidence: 99%